2020
DOI: 10.1016/j.amjcard.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Health and Outcomes in Cancer Patients Receiving Immune Checkpoint Inhibitors

Abstract: Whether cardiovascular (CV) disease is associated with clinical outcomes in cancer patients receiving immunotherapy is unknown. We reviewed the Mayo Clinic database for all cancer patients who received an immune checkpoint inhibitor (ICI). Multivariate logistic regression analysis, survival analyses, and Cox proportional-hazards models were formulated. Between March, 2010 and July, 2019, 3,326 patients received ICI. Mean patient age was 63.5 years (range: 16 to 96 years). In a Cox proportional-hazards model, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 13 publications
4
73
1
5
Order By: Relevance
“…In line with previous studies reporting a higher risk of ICI-related myocarditis with pre-ICI home angiotensin-converting enzyme inhibitor or angiotensin receptor blocker treatment, a history of heart failure and/or a history of acute coronary syndrome [7,10], the results of our study provide further support to the hypothesis that pre-existing CV risk factors and/or CV diseases are associated with the reporting of myocarditis in patients treated with ICIs. In clinical practice, cancer patients with pre-existing CV conditions could thus be exposed to higher risk of developing myocarditis upon treatment with ICIs, and might benefit from a more intensive cardiac surveillance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with previous studies reporting a higher risk of ICI-related myocarditis with pre-ICI home angiotensin-converting enzyme inhibitor or angiotensin receptor blocker treatment, a history of heart failure and/or a history of acute coronary syndrome [7,10], the results of our study provide further support to the hypothesis that pre-existing CV risk factors and/or CV diseases are associated with the reporting of myocarditis in patients treated with ICIs. In clinical practice, cancer patients with pre-existing CV conditions could thus be exposed to higher risk of developing myocarditis upon treatment with ICIs, and might benefit from a more intensive cardiac surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes (as a CV risk factor) and angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (as pre-ICI home drugs for underlying CV diseases) were more commonly found in patients with ICI-related myocarditis than in patients without such an ADR in a case-control study within the medical records from a multicenter registry [7]. Data from the Mayo Clinic further revealed that a history of heart failure and a history of acute coronary syndrome were also associated with a higher risk of ICI-related myocarditis [10].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ICIs can induce immune-mediated cardiotoxicity, including myocarditis, pericarditis, heart failure, arrhythmias, and MI. These events are uncommon, occurring in <3% of patients who receive ICIs, but carry high risk of mortality (90).…”
Section: Immune System Activationmentioning
confidence: 99%